Training the trainees in robotic surgery – a pilot scheme in the United Kingdom - Mohammed Al-Ani; Samuel Massias; Panduka Jayawardena; Esha Khanderia; Joshua Franklyn; Khawar Hashmi; Vanash Patel (BMC Medical Education)
Abstract Background Training in robotic colorectal surgery is predominantly confined to senior trainees and consultants. The lack of robotic training of the general surgical specialist trainee (ST) in the formative stages of training has led to widespread discontent among them. This paper describes a pilot scheme to establish a robotic training programme for general surgical STs in a district general hospital. Methods Six STs were enrolled between May 2023 and October 2023. A training programme was established using the CMR Surgical Versius robotic system, which consisted of online modules, a first assist course, performance-tracked virtual simulation, basic surgical skills assessment, and live operating. The programme was evaluated using the Royal College of Surgeons Participant Feedback Questionnaire (Likert scale 1–5). Results Trainees ranging from ST4 to ST8 took a median of 4.5 days (IQR 2) to complete 16 performance-tracked virtual simulation tasks. There was a significant variance in the number of attempts to pass each task (p < 0.0001), with STs finding endoscope control, suturing and knot-tying the hardest tasks to pass. There was a significant variance between the STs in the number of attempts to pass all the tasks (p = 0.02), with the ST4 trainee performing significantly better than the ST7 and ST8 trainees (p < 0.05). The STs participated in 43 operations (anterior resection = 13, abdominoperineal resection = 4, right hemicolectomy = 10, loop colostomy = 1 and cholecystectomy = 15). There were no complications related to training. Feedback on the programme was positive with a median score of 5 (IQR 0.75) for all sections of the questionnaire. Conclusions A structured robotic training programme to democratise robotic surgical training, especially among junior trainees who may not have prior laparoscopic surgical experience is safe and feasible. Replicating similar schemes in other hospitals may improve robotic access and training for STs.